Frecuency of Candida in vagina of reproductive age women - María Lucía Delmonte; Priscila Fernández; Sandra Robertiz; Evelyn González; Noris Arcaya (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2017)
Candida is considered an opportunistic pathogen that depends on specific virulence factors and host predisposing factors to cause infection. Digestive and respiratory tracts, along with the genital mucosa (vagina), are the most important reservoirs in humans and origin of endogenous candidiasis. The aim of this study was, determine the prevalence of Candida in vagina of women  of reproductive age. 107 vaginal samples were analyzed in the unit of Dental Medical Services at the University of Zulia, on those samples was performed direct examination with methylene blue stain 0.25% and grown in a Sabouraud culture medium, incubated at 28° C for 8 days. The Petri dishes that showed characteristic Candida growth were performed the respective morphological and physiological tests for identification and as a confirmatory test, Chromo Agar selective medium. Of the total number of samples tested, 24 were positive. The highest frequency was in women aged 41- 45 years (25%), followed by the age groups ranging from 21-25años (20.83%) and 26 to 30 years (20.83%). This research showed that the presence of Candida is independent of the diet, presence of symptoms, diabetes and medicament administration.